Design and development of a parallel robot for 3D additive manufacturing - Soo, Kok Xian (2015)
The conventional 3D printers is a stack-up configuration additive manufacturing process. It prints the material layer by layer but due to the heavy motor that moves along the printing, the printing speed is slow. A delta robot configuration has the advantage of high speed movement and thus is implemented in 3-D printer to expand the possibility of 3-D printing. The model had been redesigned and reconstructed to allow the movement in 6 degrees of freedom instead of the original 3 degrees of freedom. The extruder of the 3-D printer has a larger possibility in carrying out the printing process at surfaces not parallel to the ground. Experiments are conducted on the prototype to verify the ability of the robot to move with a 6 degrees of freedom. The experiment results showed that the configuration is feasible in carrying out a 6 DOF movement. However, the accuracy and precision of the end effector can be improved by conducting further studies. The robot, is able to carry the extruder around with a redesign by substituting the heavy compartments with lighter material. However, the printing was not carried out successfully due to some limitations in the design of the extrusion; future work will need to look into a new design of the extrusion so that printing operations can take place.